Effect of organic mulches, manure and chemical fertilizers on leaf yield and economics of Eryngo (Eryngium foetidum L.) - Devi, Pangeijam Bijaya; Deb, Panna Deb; Huidrom, Huidrom Birkumar Singh (Journal of Horticultural Sciences, 2024)
Eryngo (Eryngium foetidum L.) is an important high value indigenous spice crop. Development of package of practices for its cultivation is very much required for the welfare and livelihood security of the small land holding farmers. Thus, the experiment on Effect of organic mulches, manure and chemical fertilizers on leaf yield and economics of Eryngo (Eryngium foetidum L.) was conducted at Krishi Vigyan Kendra, Utlou, Bishnupur District, Manipur during 2017-18 and 2018-19.The highest leaf yield of 10924.53kg/hain 2017-18and12069.55 kg/ha 2018-19was obtained in treatment T4 (application of vermicompost @ 2.5 tons /ha + mulching with rice straw @ 5 tons / ha) followed by the treatment T5 (application of vermicompost @ 2.5tons / ha + mulching with rice husk @ 5 tons / ha) with leaf yield of 9113.70 kg/ha and 9401.00 kg/ha in respective years. The minimum leaf yield of 3861.98 kg/ha in 2017-18 and4210.08 kg/ha in 2018-19 was obtained in T0 (Control) in which no external input was applied. There were significant variations in different treatments in leaf yield and economic return. From the pooled analysis, the highest yield of 11,497.04kg/ha and net return of Rs526420.56with C:Bratio 1:5.34 was obtained forT4treatment. Thus, the information generated through the present study will help to develop the scientific package of practices for cultivation of Eryngo which in turn will help to improve the economy of the small and marginal farmers of Manipur, Northeast India.